'Problem patients and physicians' failures': What it means for doctors to counsel vaccine hesitant patients in Switzerland. (June 2020) - Deml, Michael J.; Buhl, Andrea; Notter, Julia; Kliem, Paulina; Huber, Benedikt M.; Pfeiffer, Constanze; Burton-Jeangros, Claudine; Tarr, Philip E.
Abstract: This article reports on our qualitative inquiry into the meanings biomedically trained doctors in Switzerland attach to treating vaccine hesitant (VH) and underimmunized patients. With support from social science literature on 'good' and 'bad' patients and doctors, we explore how both doctors and patients cross the boundaries of these conceptual categories in situations involving vaccine hesitancy and underimmunization. The doctors we interviewed (N = 20) and observed (N = 16 observations, subsample of 6 doctors from the interview sample) described how they screened, measured, and diagnosed patients' levels of vaccine hesitancy. Our results emphasize the meanings doctors associated with counseling hesitant patients, especially while managing their own professional responsibilities, legitimacy, and reputations among colleagues and patients. Doctors' discourses constructed the figure of 'problem patients, ' characterized through their (potential) non-adherence to vaccination recommendations, desire for lengthy consultations and individualized counseling, and dogmatic ideologies running contra to biomedicine. Discussions around the dilemmas faced by doctors in vaccination consultations brings to the fore several key, yet underdiscussed, paradoxes concerning VH, patient-doctor relationships, and the constructs of 'good'/'bad' doctors and patients. These paradoxes revolve around expectations in Western societies for 'good' patients to be autonomous health-information seekers and active participants in clinical encounters, which research shows to be the case for many VH and underimmunizing individuals. However, in the eyes of many vaccination advocates and proponents of biomedical approaches, VH patients become 'bad' patients thru their risk of non-adherence, which has implications for the population at large. In these consultations, doctors find themselves conflicted around the expectations to promote vaccination while, at the same time, being active listeners and good communicators with those who question their biomedical training and legitimacy. Understanding these paradoxes highlights the need to better support HCPs in addressing VH in clinical practice. Highlights: Vaccine hesitancy stimulates discussion of paradoxes of good/bad doctors/patients. Biomedical doctors sometimes perceive vaccine hesitant patients as problematic. Biomedical doctors' vaccination approaches have implications for their reputations. Qualitative interviews and ethnographic observations with biomedical doctors.